DALI: Vitamin D and lifestyle intervention for gestational diabetes mellitus (GDM) prevention: an European multicentre, randomised trial – study protocol - Judith G. M. Jelsma; Mireille N. M. van Poppel; Sander Galjaard; Gernot Desoyé; Rosa Corcoy; Roland Devlieger; André Van Assche; D. Timmerman; Goele Jans; Jürgen Harreiter; Alexandra Kautzky‐Willer; Peter Damm; et al. (2013)
Background: Gestational diabetes mellitus (GDM) is an increasing problem world-wide. Lifestyle interventions and/or vitamin D supplementation might help prevent GDM in some women.Methods/design: Pregnant women at risk of GDM (BMI≥29 (kg/m 2)) from 9 European countries will be invited to participate and consent obtained before 19+6 weeks of gestation. After giving informed consent, women without GDM will be included (based on IADPSG criteria: fasting glucose<5.1mmol; 1 hour glucose <10.0 mmol; 2 hour glucose <8.5 mmol) and randomized to one of the 8 intervention arms using a 2×(2×2) factorial design: (1) healthy eating (HE), 2) physical activity (PA), 3) HE+PA, 4) control, 5) HE+PA+vitamin D, 6) HE+PA+placebo, 7) vitamin D alone, 8) placebo alone), pre-stratified for each site. In total, 880 women will be included with 110 women allocated to each arm. Between entry and 35 weeks of gestation, women allocated to a lifestyle intervention will receive 5 face-to-face, and 4 telephone coaching sessions, based on the principles of motivational interviewing. The lifestyle intervention includes a discussion about the risks of GDM, a weight gain target <5kg and either 7 healthy eating 'messages' and/or 5 physical activity 'messages' depending on randomization. Fidelity is monitored by the use of a personal digital assistance (PDA) system. Participants randomized to the vitamin D intervention receive either 1600 IU vitamin D or placebo for daily intake until delivery. Data is collected at baseline measurement, at 24-28 weeks, 35-37 weeks of gestation and after delivery. Primary outcome measures are gestational weight gain, fasting glucose and insulin sensitivity, with a range of obstetric secondary outcome measures including birth weight.Discussion: DALI is a unique Europe-wide randomised controlled trial, which will gain insight into preventive measures against the development of GDM in overweight and obese women.